Plasma exchange in the treatment of sepsis: a review of randomized clinical trials - D.D. Kartashev; D.L. Shukevich (Russian Journal of Anesthesiology and Reanimatology, 2026)
Plasma exchange is one of the extracorporeal treatment methods for sepsis. Despite extensive research of plasma exchange, changes in definitions of sepsis, heterogeneous patient populations and differences in study design make it difficult to define the target population for this method. The purpose of this review was to analyze publications devoted to plasma exchange for the treatment of sepsis. Searching was conducted in PubMed database using appropriate keywords. Final searching session was conducted on February 5, 2026. Primary selection yielded 8.107 references. After analysis of titles and abstracts, we excluded 8.099 studies without necessary data. The final group included 8 studies.